2014
DOI: 10.1152/ajpendo.00219.2014
|View full text |Cite
|
Sign up to set email alerts
|

Composition and function of macroencapsulated human embryonic stem cell-derived implants: comparison with clinical human islet cell grafts

Abstract: Therapy Consortium EU-FP7. Composition and function of macroencapsulated human embryonic stem cell-derived implants: comparison with clinical human islet cell grafts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
94
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(100 citation statements)
references
References 35 publications
4
94
0
2
Order By: Relevance
“…These results and comparison with human islets have been reported [22]. Here, expression of HLA was assessed on the cell surface of hESC-PEs and hESC-ECs.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…These results and comparison with human islets have been reported [22]. Here, expression of HLA was assessed on the cell surface of hESC-PEs and hESC-ECs.…”
Section: Resultssupporting
confidence: 52%
“…Preproinsulin (PPI)-specific T cell clone 1E6 generation was described previously [23]. Briefly, PBMCs from an individual with type 1 diabetes were stimulated with PPI [15][16][17][18][19][20][21][22][23][24] peptide. PPI-specific cytotoxic T lymphocytes (CTLs) were sorted by FACS and expanded.…”
Section: Methodsmentioning
confidence: 99%
“…However, PEG-encapsulation is ineffective in protecting islets from cytokine-mediated cell injury and it has also been demonstrated that PEG is less biocompatible than alginate and similar hydrogels [86]. Nanolayers composed of alginate and chitosan [158], membranes made of polylysine and poly(glutamic acid) [87], poly(L-lysine)-poly(ethylene glycol) (biotin) (PPB) and streptavidin (SA) [160], complement receptor-1 and heparin [88], and PEG lipid and poly(vinyl alcohol) (PVA) [89,90] are some of the many biomaterials currently being evaulated for use in stem cell and islet nanoencapsulation.…”
Section: Nanoencapsulationmentioning
confidence: 99%
“…Pancreatic stem cells [160,161], hESCs [162][163][164], induced pluripotent stem cells (iPSCs) [165][166][167][168][169], mesenchymal [170][171][172][173][174] and adipose-derived stem cells (ADSCs) [175,176] have all been used to derive islet-like cell clusters or insulin-producing cells (IPCs) that are viable, express markers similar to terminally differentiated β-cells (Insulin, GLUT2) and are able to respond to a glucose challenge. These cells have all demonstrated good function after encapsulation within bioencapsulation devices and several in vivo studies have also been conducted.…”
Section: Recent Developments In Stem Cell Therapy For T1dmentioning
confidence: 99%
See 1 more Smart Citation